Personality Factors and Subjective Cognitive Decline: The FACEHBI Cohort. (19th February 2020) - Muñoz, Nathalia; Gomà-i-Freixanet, Montserrat; Valero, Sergi; Rodríguez-Gómez, Octavio; Sanabria, Angela; Pérez-Cordón, Alba; Hernández, Isabel; Marquié, Marta; Mir, Iolao; Martín, Elvira; Benaque, Alba; Ruiz, Agustín; et al.
Abstract : Individuals with subjective cognitive decline (SCD) have the perception of memory problems without showing impairment on standardized cognitive tests. SCD has been associated with an increased risk of developing Alzheimer's disease (AD). Neuroticism and openness personality dimensions have also been associated with SCD and AD. From the aforementioned, we aimed to ascertain whether the dimensions and traits defined by the Zuckerman-Kuhlman Personality Questionnaire (ZKPQ) differentiate between individuals with SCD and the general population (GP). A total of 187 participants with SCD and mild affective symptomatology recruited from the Fundació ACE Health Brain Initiative (FACEHBI) project completed the ZKPQ. Each SCD participant was matched by sex and age to an individual from the GP. Both samples included 71 men and 116 women with a mean age of 65.9 years. Results indicated that the SCD group scored significantly lower in Neuroticism-Anxiety and Activity than the GP group. Only Activity remained statistically significant in a multivariate analysis. These findings suggest that individuals with SCD have a low energy level and a dislike for an active and busy life. From the obtained results and knowing additional physical activities may delay the conversion from normal aging to cognitive impairment, we encourage promoting this lifestyle in daily routine. The assessment of personality may result in an SCD plus feature, which may serve as an upgrading strategy for future research.